-7(x+2)+3x+7=5x+12

Simple and best practice solution for -7(x+2)+3x+7=5x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+2)+3x+7=5x+12 equation:


Simplifying
-7(x + 2) + 3x + 7 = 5x + 12

Reorder the terms:
-7(2 + x) + 3x + 7 = 5x + 12
(2 * -7 + x * -7) + 3x + 7 = 5x + 12
(-14 + -7x) + 3x + 7 = 5x + 12

Reorder the terms:
-14 + 7 + -7x + 3x = 5x + 12

Combine like terms: -14 + 7 = -7
-7 + -7x + 3x = 5x + 12

Combine like terms: -7x + 3x = -4x
-7 + -4x = 5x + 12

Reorder the terms:
-7 + -4x = 12 + 5x

Solving
-7 + -4x = 12 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-7 + -4x + -5x = 12 + 5x + -5x

Combine like terms: -4x + -5x = -9x
-7 + -9x = 12 + 5x + -5x

Combine like terms: 5x + -5x = 0
-7 + -9x = 12 + 0
-7 + -9x = 12

Add '7' to each side of the equation.
-7 + 7 + -9x = 12 + 7

Combine like terms: -7 + 7 = 0
0 + -9x = 12 + 7
-9x = 12 + 7

Combine like terms: 12 + 7 = 19
-9x = 19

Divide each side by '-9'.
x = -2.111111111

Simplifying
x = -2.111111111

See similar equations:

| -15e+7p-(-11e)+(-13p)= | | x=7/2 | | 12x+3x=2-6+4x | | 2(7x-9)=14x-18 | | 3/8+b/8=5/12 | | 8(n-1)=-24 | | 2.5z-1.5z+8.7=7.2 | | -3x+6-5(x-1)=-5x(2x-4)+5 | | 2/6=a/2 | | 0.12(y-9)+0.18y=0.02y-0.01 | | x/36=2/9 | | 4x-3=6x+5 | | 32/4=x/2 | | 9x+3=7x+25 | | s/t-q/t=1 | | 4(x+3)-2x=-3-x | | -2/3t+2t=6/5t+2/5 | | 1.5t+2=4 | | -7.8x=-156 | | -9=-h/-12+5 | | 7x-14x=3x+8x-18 | | -29+n=9 | | 8y+15=12y-9 | | 5/2x-11/2=19/2 | | 23=-14+r | | 4x-7+6x-13=180 | | a-28=28 | | 9(d-2)+2= | | 5.5-4.72x-1.3x=30.784 | | 9(2x-8)=0 | | q+12=23 | | 2w+5+2w-10=90 |

Equations solver categories